Reforming Intergovernmental Fiscal Relations and the Rebuilding of Indonesia - James Alm (Published by Edward Elgar Publishing Limited, 2004)
Indonesia is currently facing some severe challenges, both in political affairs and in economic management. One significant part of this challenge is the decentralization program, whose laws were first passed in May 1999 and subsequently put in operation in January 2001. For political reasons, this program was enacted and implemented in an extraordinarily short period of time, and has often been referred to as the ‘Big Bang’ decentralization. With the resignation of President Suharto in 1998, many provinces and regions in Indonesia demanded more decentralized governance. In its own transition from a corrupt and highly centralized dictatorship to a democratic market economy, the process of decentralization in Indonesia was perceived by many as a new bridge to democracy and to a more efficient and fairer government. The process of decentralization is now well underway, and it promises to have many wide-ranging effects. However, there remain numerous questions about this program. This edited volume is a collection of original papers, written by a group of scholars with direct experience in Indonesia and policy makers who have been personally involved in the decentralization process. The chapters in the volume take a hard look at the many effects of decentralization on economic and political issues in Indonesia.1 They cover the wide impacts of decentralization: the political and economic forces that contributed to the passage of the decentralization laws, the assignment of expenditure and revenue functions across levels of government, the design of intergovernmental transfers, the control of local government borrowing, natural resource revenue sharing, and an assessment of the progress that has been made in the initial years of the decentralization.